Gender and major choice within economics: Evidence from Europe. (November 2020) - Arnold, Ivo J.M.
Abstract: A large literature studies the underrepresentation of female students in economics majors in the United States. This paper adds to this literature by examining gender differences in major choice within an economics bachelor program at a European university. Using a large sample of major students, we document gender differences in the choice of subfields. Female students are strongly underrepresented in finance and overrepresented in accounting. We also test the grade sensitivity hypothesis, according to which the major choice of female students is more responsive to grades. For almost all subfields, major choice is significantly and positively related to the academic performance in the corresponding introductory course(s). The evidence that female students are more sensitive to grades is, however, weak.